Î²-Catenin overexpression causes an increase in inflammatory cytokines and NF-ÎºB activation in cardiomyocytes - Lin, J. C.; Chang, R-L.; Chen, Y-F.; Yang, J-J.; Baskaran, R.; Chung, L-C.; Chen, R-J.; Day, C. H.; Vijaya Padma, V.; Huang, C-Y. (Cellular and Molecular Biology, 2016)
Î²-Catenin has been implicated in various developmental and physiological processes. Defective Wnt signaling can result in different cardiac and vascular abnormalities and is activated under pathological conditions such as inflammation and obesity. In this study, roles of Î²-catenin in inflammation in cardiomyocytes were investigated. 10 samples from hearts of patients with acute infarction and 10 from normal ones were collected in order to access roles of Î²-catenin in cardiomyocytes. H9c2 cardiomyoblasts and primary neonatal rat cardiomyocytes were transfected with porcine cytomegalovirus (pCMV)-Î²-catenin plasmid in order to overexpress Î²-catenin. Protein level of Î²-catenin protein was increased in human acute infarction tissues compared to ones from normal patients. The transcription factor had increased nuclear localization in cardiomyocytes of the Wistar rats with cardiac hypertension. Furthermore, expression of fibrosis protein markers increased. Protein expression of Î²-catenin was increased in human acute infarction inflammatory heart tissues and in hearts of inflammatory obesity rats. After pCMV-Î²-catenin plasmid was transfected in a dose-dependent manner, inflammation protein markers, TNF-Î± and IL-8, were upregulated in hypertensive neonatal rat cardiomyocytes and H9c2 cardiomyoblasts. In addition, overexpression of Î²-catenin induced activation and nuclear localization of NF-ÎºB. Therefore, Î²-catenin is a potential molecular target for treatment of inflammation and fibrosis in cardiomyocytes.